2017
DOI: 10.20333/2500136-2017-1-17-25
|View full text |Cite
|
Sign up to set email alerts
|

Biological Markers of the Antiepileptic Drugs Efficacy and Safety: Pharmacogenetics and Pharmacokinetics

Abstract: государственный медицинский университет им. проф. В. Ф. Войно-Ясенецкого, Красноярск, 660022, Российская Федерация p%'>,%. Проблема недостаточной эффективности противоэпилептических препаратов (ПЭП) и риск возникновения клинически значимых побочных явлений является, по-прежнему, актуальной. У больных эпилепсией выявляются значительные индивидуальные различия терапевтического эффекта ПЭП-от нормальной и повышенной чувствительности до резистентности. Существует необходимость разработки персонализированных терапе… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
3
Order By: Relevance
“…JME is a widespread form of GGE, which includes myoclonic seizures, sometimes other seizure types (generalized tonic-clonic seizures, absences), onset in adolescence, and typical EEG changes as generalized spike and polyspike waves 4-6 Hz discharges with a normal background EEG [16,17]. The age of onset of JME covers a wide range from 8 to 36 years of age, with a peak onset from 12 to 18 years of age [4,5,18].…”
Section: Discussionmentioning
confidence: 99%
“…JME is a widespread form of GGE, which includes myoclonic seizures, sometimes other seizure types (generalized tonic-clonic seizures, absences), onset in adolescence, and typical EEG changes as generalized spike and polyspike waves 4-6 Hz discharges with a normal background EEG [16,17]. The age of onset of JME covers a wide range from 8 to 36 years of age, with a peak onset from 12 to 18 years of age [4,5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that human cytochrome P450 (CYP) isoenzymes play a crucial role in VPA metabolism [ 62 , 63 ]. A key CYP-mediated branch of the VPA pathway produces the metabolites 4-hydroxy(OH)-VPA and 5-OH-VPA via hepatic cytochrome P450 isoenzymes CYP2C9, CYP2B6, and CYP2A6.…”
Section: Pharmacometabolomics and Pharmacogenomics Of Valproic Acidmentioning
confidence: 99%
“…ìàêîëîãèè [2][3][4]. Îöåíêó ýôôåêòèâíîñòè íîâûõ ÏÝÏ íà ñòàäèè äîêëèíè÷åñêèõ èññëåäîâàíèé êëàññè÷åñêè îñóùåñòâëÿþò íà aeèâîòíûõ ìîäåëÿõ ýïèëåïñèè è ñïðîâîöèðîâàííûõ ðàçëè÷íûìè ìåòîäàìè ñóäîðîaeíûõ ïðèïàäêîâ.…”
Section: __________________________unclassified
“…Îöåíêó ýôôåêòèâíîñòè íîâûõ ÏÝÏ íà ñòàäèè äîêëèíè÷åñêèõ èññëåäîâàíèé êëàññè÷åñêè îñóùåñòâëÿþò íà aeèâîòíûõ ìîäåëÿõ ýïèëåïñèè è ñïðîâîöèðîâàííûõ ðàçëè÷íûìè ìåòîäàìè ñóäîðîaeíûõ ïðèïàäêîâ. Ñ ýòîé öåëüþ èñïîëüçóþòñÿ ðàçëè÷íûå ìåòîäèêè: ìåõàíè÷åñêèå (òðàâìàòèçàöèÿ ñòðóêòóð öåíòðàëüíîé íåðâíîé ñèñòåìû, áîëåâîå âîçäåéñòâèå); ôèçè÷åñêèå (çâóêîâûå è ñâåòîâûå ðàçäðàaeåíèÿ, ãèïåðòåðìèÿ, âîçäåéñòâèå ýëåêòðè÷åñòâîì); àïïëèêàöèè ìåòàëëîâ (íàíåñåíèå íà ïîâåðõíîñòü êîðû ãîëîâíîãî èëè èíòðàöåðåáðàëüíîå ââåäåíèå ñîåäèíåíèé ìåòàëëîâ: ãèäðîêñèäà àëþìèíèÿ, ñóëüôàòà öèíêà, õëîðèäà êîáàëüòà); õèìè÷åñêèå ìåòîäû; à òàêaeå ãåíåòè÷åñêèå ìîäåëè ýïèëåïñèè [4,5].…”
Section: __________________________unclassified